2009
DOI: 10.1016/j.brainresrev.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor in experimental stroke and its effects on infarct size and functional outcome: A systematic review

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 56 publications
(66 reference statements)
5
40
0
Order By: Relevance
“…Additionally, there were acinar and ductal diameters significant decrease than MTX group and nonsignificant increase versus group I. These findings are supported by the previously reported therapeutic effect of G-CSF on liver, kidney and brain lesions and irradiated salivary glands [15,[57][58][59] . Such G-CSF preservative influence was explained by its BMHSCs mobilizing effect [60] supported in this work by BMHSCs significant increase in Neupogen-treated group compared to MTX group.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, there were acinar and ductal diameters significant decrease than MTX group and nonsignificant increase versus group I. These findings are supported by the previously reported therapeutic effect of G-CSF on liver, kidney and brain lesions and irradiated salivary glands [15,[57][58][59] . Such G-CSF preservative influence was explained by its BMHSCs mobilizing effect [60] supported in this work by BMHSCs significant increase in Neupogen-treated group compared to MTX group.…”
Section: Discussionsupporting
confidence: 87%
“…The regenerative potential by G-CSF, apart from its neuroprotective power in the acute phase of stroke, has been shown in various studies. [13][14][15] In the present study, we can show that postischemic G-CSF treatment, in fact, causes an increased functional outcome concerning motor and sensorimotor qualities. However, its combination with CIMT, by concurrent application as well as by sequential treatment, failed to further enhance the beneficial effect.…”
Section: Discussionsupporting
confidence: 58%
“…To date, G-CSF PBSC mobilization has been generally regarded as a practical and feasible source of cells for therapeutic angiogenesis [27][28][29]. However, a recent metaanalysis reported that G-CSF infusion alone had no significant clinical benefit in myocardial infarction [30], and it was reported that G-CSF-mobilized PBSCs were less effective in inducing ulcer healing than were BMSCs [31].…”
Section: Introductionmentioning
confidence: 99%